Rapid Determination of Carbohydrates in Heroin Drug Seizures Using Capillary Electophoresis with Short-End Injection - Anastos, N.; Barnett, N.; Lewis, Simon; Pearson, J.; Kirkbride, K. (ASTM International, 2005)
A simple and rapid method for the analysis of carbohydrates in heroin samples by capillary electrophoresis utilizing a borate complexation method is described. Separations were performed using an uncoated fused silica capillary, 50 cm × 50 µm I.D. × 360 µm O.D. with an effective separation length of 9 cm. The system was run at 60?C with an applied voltage of -8 kilovolts. Injection of each sample was for 1 sec at -50 mbar. UV detection was employed with the wavelength set at 195 nm. The background electrolyte consisted of 65 mM borate, pH 12.0. Samples and standards were prepared in the run buffer containing 2 mg/mL of mannose as an internal standard. Under these conditions a test mixture containing glucose, sucrose, lactose, mannitol and mannose as an internal standard was resolved within 5 min. The method was used to determine the concentration of carbohydrates in heroin seizure samples and synthetic heroin samples. The results were in good agreement with the reported values.